P48 Covid-19 associated arterial embolic events: a multicenter retrospective study. (29th August 2022) - Schinz, D; Ploch, M; Saleh, A; Ibrahim, T; Paprottka, P; Zimmer, C; Boeckh-Behrens, T
Abstract : Background and aims: During the course of the pandemic, it became clear that COVID-19 should be regarded as a systemic disease, particularly affecting the coagulation system with a high incidence of arterial thrombotic events (ATE).The aim of this study was to investigate the incidence and characteristics of ATE in hospitalized patients with COVID-19 using clinical and imaging data. Methods: From the beginning of the COVID-19 pandemic in January 2020 to May 2021, databases of five German tertiary-care centers were searched for patients with coincidental ATEs associated with a COVID-19 disease. ATEs were examined regarding their localization, time of occurrence, radiographic characteristics, and associations with clinical data and laboratory parameters. Results: Out of 3267 COVID-19 patients, 102 patients (110 events; median age 76(11–102)) presented with ATEs (3.1%). Localization included cardiac(n=51), brain(n=43), peripheral(n=7), intestinal(n=3), precerebral arteries(n=3), aorta(n=1), kidney(n=1), and spleen(n=1). Some ATE showed patterns of massive thrombi with long-floating portions (Figure 1). Elevated CRP (median 45 mg/L) and fibrinogen levels (median 477 mg/dL) prior to ATEs were detected. ATEs occurred at a median of 4 (-17–58) days after the onset of typical primary symptoms of COVID-19. Conclusion: COVID-19 is associated with an increased rate of ATEs generally affecting all areas of the arterial system and partially with an unusual radiographic pattern. Most clinically detectable ATEs occurred in arterial vessels of the brain and heart, although some emboli were detected in atypical locations and in young patients. Approximately the first week after symptom onset seems to be the main critical period for the occurrence of an ATE. References: De Roquetaillade C, Chousterman BG, Tomasoni D, et al . Unusual arterial thrombotic events in Covid-19 patients. Int J Cardiol 2021 Jan 15;323:281–284. Do you have any conflict of interest to declare? : No